2004
DOI: 10.1007/s00441-004-0972-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of the dopaminergic nigrostriatal system in aging

Abstract: Although the maximum human lifespan has not increased in recent history, average life expectancy has risen dramatically since the beginning of the last century. Lengthening of lifespan has little merit if the quality of life is not preserved. In the elderly, the decline in memory and cognitive abilities is of great concern, as is motor weakening, which increases with age. The dopaminergic system mediates some aspects of manual dexterity, in addition to cognition and emotion, and may be especially vulnerable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 87 publications
8
53
0
3
Order By: Relevance
“…Nevertheless, the difference between the 7 youngest (mean age: 27; 378,000 neurons) and the 7 oldest (mean age: 82; 256,000) subjects was not significant. Although the absolute numbers of pigmented neurons in the SN in young subjects in our series are different from those reported in two previous stereological studies [7,29], our results are consistent with an age-associated loss of pigmented neurons in the SN [7,29,41]. Although it should be noted that other stereological studies have found no age-related losses of pigmented SN neurons, those same studies have reported marked decreases in the number of neurons expressing specific phenotypic markers [8,9].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Nevertheless, the difference between the 7 youngest (mean age: 27; 378,000 neurons) and the 7 oldest (mean age: 82; 256,000) subjects was not significant. Although the absolute numbers of pigmented neurons in the SN in young subjects in our series are different from those reported in two previous stereological studies [7,29], our results are consistent with an age-associated loss of pigmented neurons in the SN [7,29,41]. Although it should be noted that other stereological studies have found no age-related losses of pigmented SN neurons, those same studies have reported marked decreases in the number of neurons expressing specific phenotypic markers [8,9].…”
Section: Discussionsupporting
confidence: 52%
“…Our estimation of total number of pigmented neurons in younger subjects is higher than that of previous studies (adjusted for one side of the SN): Ma et al [29] ∼150,000, and Cabello et al [7] 189,000. These differences can be attributed to several factors including the use of different embedding media, histological stains, stereological methods, but more importantly the delineation of the boundaries of the SN region [41]. In the older controls, we estimated a mean of 305,000 pigmented neurons (unilateral), a number slightly higher than the 275,000 neurons (adjusted for one side of the SN) estimated by Pakkenberg et al [38] in older controls (mean age: 81).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is undoubtedly the single strongest risk factor for PD (20,37). Stereological estimates of normal aging related cell death in humans argue that SNc DA neurons at a higher risk than other neurons in the absence of environmental toxins or pathogens, as they are lost at a significantly higher rate than many other types of neurons (some of which show no appreciable loss over a 6-7-decade span) (109). In mammals with significantly shorter lifespans, loss of SNc DA neurons with age has not been seen reliably, but there is a clear decline in phenotypic markers with age that matches that seen in PD, as well as an increased susceptibility to toxins (4,23,54,60,61,76).…”
Section: Pd Ros and Agingmentioning
confidence: 99%
“…This perspective predicts that there should be functional impairment or loss of SNc DA neurons with normal aging. Stereological estimates of normal aging-related cell death in humans argue that SNc DA neurons at a higher risk than many other types of neuron (109). In mammals with significantly shorter lifespans, loss of SNc DA neurons with age has not been seen reliably, but there is a clear decline in phenotypic markers with age that matches that seen in PD, as well as an increased susceptibility to toxins (4,23,54,61,76).…”
Section: The Interplay Between Pan-cellular and Cell-specific Risk Famentioning
confidence: 99%